Power sources and supplies world class designs - Brown, Marty, 1951- (Newnes/Elsevier, 2008)
Newnes has worked with Marty Brown, a leader in the field of power design to select the very best design-specific material from the Newnes portfolio. Marty selected material for its timelessness, its relevance to current power supply design needs, and its real-world approach to design issues. Special attention is given to switching power supplies and their design issues, including component selection, minimization of EMI, toroid selection, and breadboarding of designs. Emphasis is also placed on design strategies for power supplies, including case histories and design examples. This is a book that belongs on the workbench of every power supply designer! *Marty Brown, author and power supply design consultant, has personally selected all content for its relevance and usefulness *Covers best design practices for switching power supplies and power converters *Emphasis is on pragmatic solutions to commonly encountered design problems and tasks.
Keywords: Electric power supplies to apparatus -- Design and construction.; Electronic apparatus and appliances -- Power supply.; elektronické knihy; electronic books